The politics of environmental policy: haze pollution, ASEAN, and the way forward - Bama Andika Putra; Bama Andika Putra (Frontiers in Sustainable Cities)
One of the lingering environmental issues faced in Southeast Asia is transboundary haze due to peatland fires. The issue is primarily evident in the Southern sub-region of ASEAN but affects the entirety of the Southeast Asian region. Recent spikes in haze since 2023 and ASEAN’s inability to adopt enforcing pronouncements and mediate the political ‘blame game’ between ASEAN member states lays the foundation for alternative approaches to curtail the environmental crisis. This empirical explanatory study utilizes primary and secondary data between 2014 and 2024 relevant to the political dynamics of haze pollution regulation in Southeast Asia. It is recommended that an ASEAN code of conduct be introduced to elevate the importance of transboundary haze regulations in Southeast Asia. A moderate level of its implementation grants ASEAN member states the freedom to determine the time period and form of domestic regulations to be practiced. In ensuring greater stakeholder accountability and participation, it is also recommended that ASEAN member states provide incentives for private entities adopting sustainable management practices of peatlands and sanction stakeholders who display non-compliance.